(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This research introduces an AI-driven automotive marketplace platform designed to enhance the vehicle buying and selling ecosystem through intelligent automation and data-driven decision-making. The system enables image-based vehicle search using computer vision models capable of extracting vehicle attributes such as make, model, variant, and features directly from user-uploaded images. The platform integrates an AI-powered conversational calling agent that analyzes customer intent, budget, and usage patterns to provide personalized vehicle recommendations and automated test drive booking. Experimental evaluation demonstrates that the proposed system achieves 93.4% vehicle recognition accuracy, an R² score of 0.87 for price prediction, and an average recommendation response time below 2.1 seconds, improving decision-making efficiency compared to traditional automotive marketplace platforms.